PANCASILA ANALYSIS OF SOCIAL JUSTICE AND HUMAN RIGHTS: JESSICA WONGSO'S CASE STUDY - Ratu Fajar Diva Malika Bahagia; Siti Maizul Habibah (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
Pancasila is the legal basis for all legal and constitutional resources in the country of Indonesia. All behavior in nationality will be governed in pancasila, especially in legal and political spheres. At present, a Indonesia tela has become an easy target for law-enforcement politicians. The law is blunt up and blunt down, can we see in the case of Jessica Wongso’s cyanide coffee. The case has been going on since 2016 - now, the final decision of the panel of judges remains a raging debate throughout Indonesia. The pancasila implementation in the case of Jessica Wongso’s is very correct with the item of 5, which is social justice for all people of Indonesia. Mirna's death was thought to have been caused by a cyanide contaminated coffee intake. Before the police put a suspect in the murder case, mass media, especially online media, together accused Jessica Wongso, as many of mirna's friends in gulping down the coffee, as the person responsible for mirna's death. In their news, without much verification and with great haste from the phase of inquiry, inquiry, to trial, some online media have judged Jessica’s, also called the trial by the press. Especially in Jessica's case, with the hope that in the future there will be no further negative effects from the giver.